2010
DOI: 10.1105/tpc.109.072637
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic and Secretory Traffic in Arabidopsis Merge in the Trans-Golgi Network/Early Endosome, an Independent and Highly Dynamic Organelle

Abstract: Plants constantly adjust their repertoire of plasma membrane proteins that mediates transduction of environmental and developmental signals as well as transport of ions, nutrients, and hormones. The importance of regulated secretory and endocytic trafficking is becoming increasingly clear; however, our knowledge of the compartments and molecular machinery involved is still fragmentary. We used immunogold electron microscopy and confocal laser scanning microscopy to trace the route of cargo molecules, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
463
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 424 publications
(486 citation statements)
references
References 66 publications
22
463
0
1
Order By: Relevance
“…The SYP61 compartment appears to function as an EE for specific PM proteins [17]. The exact role of SYP61 is unclear, but it has been implicated in stress responses induced by abscisic acid [18], and it may be involved in trafficking of components to and from the prevacuolar compartment (PVC) [6,7,15,16,19]. In order to clarify the role of SYP61, and characterize the compartment in which it resides in endomembrane trafficking, we purified SYP61 vesicles using a novel, universally adoptable immunoisolation procedure for plants and conducted a detailed proteomic analysis of the vesicle components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SYP61 compartment appears to function as an EE for specific PM proteins [17]. The exact role of SYP61 is unclear, but it has been implicated in stress responses induced by abscisic acid [18], and it may be involved in trafficking of components to and from the prevacuolar compartment (PVC) [6,7,15,16,19]. In order to clarify the role of SYP61, and characterize the compartment in which it resides in endomembrane trafficking, we purified SYP61 vesicles using a novel, universally adoptable immunoisolation procedure for plants and conducted a detailed proteomic analysis of the vesicle components.…”
Section: Introductionmentioning
confidence: 99%
“…The TGN is considered an early endosome (EE) compartment because it is rapidly labeled with the endocytic marker FM4-64 [5]. It is implicated in endocytic, secretory trafficking and retromermediated recycling of vacuolar sorting receptors (VSRs) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Golgiderived structures like those in nev mutant flowers have also been seen in pollen mutants affecting the a1 subunit (VHA-a1) of the Arabidopsis vacuolar H + -ATPase proton transporter or when cells are treated with a specific V-ATPase inhibitor, concanamycin A (Dettmer et al, 2005;Liljegren et al, 2009). Recent studies have shown that the concanamycin A-induced structures are labeled with VHA-a1 and SYP61, markers of the TGN/early endosome (Viotti et al, 2010). These results suggest the possibility that the circularized structures in nev flowers are also chimeric fusions of the Golgi cisternae and the TGN and that traffic through the TGN/early endosome is affected by mutations in NEV. Disruption of CST, EVR, or SERK1 activity appears to restore the identity and independence of the TGN from the Golgi in nev flowers Lewis et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest the possibility that the circularized structures in nev flowers are also chimeric fusions of the Golgi cisternae and the TGN and that traffic through the TGN/early endosome is affected by mutations in NEV. Disruption of CST, EVR, or SERK1 activity appears to restore the identity and independence of the TGN from the Golgi in nev flowers Lewis et al, 2010). Defects in membrane trafficking are thought to underlie the inappropriate fusion of the TGN and the Golgi, as V-ATPase-mediated endomembrane acidification is required to recruit ARF G-proteins, ARF-GEFs, and coat components involved in vesicle budding (Zeuzem et al, 1992;Aniento et al, 1996;Maranda et al, 2001;Hurtado-Lorenzo et al, 2006;Viotti et al, 2010). As an ARF-GAP, NEV may regulate the activity and recruitment of the same TGN-localized ARF G-protein(s) and adaptor molecules as the V-ATPase complex.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, the trafficking inhibitor BFA targets the Arf-GEF GNOM and induces the formation of BFA compartments (Geldner et al, 2001), most likely by homotypic fusion of the TGN (which is also an early endosome) and heterotypic fusion between the TGN and other endosomes (Dettmer et al, 2006;Lam et al, 2009;Viotti et al, 2010). Therefore, SNAREs at the TGN mayfunction in these fusion events upon BFA treatment.…”
Section: Involvement Of Tno1 In Vesicle Fusionmentioning
confidence: 99%